Angiogenesis in Adipose Tissue: The Interplay Between Adipose and Endothelial Cells - Herold, Jacqueline; Kalucka, Joanna (Frontiers in Physiology, 2021)
Obesity is a worldwide health problem, and as its prevalence increases, so does the burden of obesity-associated co-morbidities like type 2 diabetes or cardiovascular diseases (CVDs). Adipose tissue (AT) is an endocrine organ embedded in a dense vascular network. AT regulates the production of hormones, angiogenic factors, and cytokines. During the development of obesity, AT expands through the increase in fat cell size (hypertrophy) and/or fat cell number (hyperplasia). The plasticity and expansion of AT is related to its angiogenic capacities. Angiogenesis is a tightly orchestrated process, which involves endothelial cell (EC) proliferation, migration, invasion, and new tube formation. The expansion of AT is accelerated by hypoxia, inflammation, and structural remodelling of blood vessels. The paracrine signalling regulates the functional link between ECs and adipocytes. Adipocytes can secrete both pro-angiogenic molecules, e.g.: tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), or VEGF, and anti-angiogenic factors, e.g.: serpins. If the pro-angiogenic molecules dominate, the angiogenesis is dysregulated and the endothelium becomes dysfunctional. However, if anti-angiogenic molecules are overexpressed relative to the angiogenic regulators, the angiogenesis is repressed, and AT becomes hypoxic. Furthermore, in the presence of chronic nutritional excess, endothelium loses its primary function and contributes to the inflammation and fibrosis of AT, which increases the risk for CVDs. This review discusses the current understanding of ECs function in AT, the cross-talk between adipose and ECs, and how obesity can lead to its dysfunction. Understanding the interplay of angiogenesis with AT can be an approach to therapy obesity and obesity-related diseases like CVDs.